Research on the Optimization Design of Variable Cross-section OilNeedle of Landing Gear Damper Based on Genetic Algorithm - Wu Zhiguang; Chen Jieping; Zhang Chenrong (Hangkong gongcheng jinzhan, 2018)
To increase landing performance of aircraft landing gear, it is needed to develop effective method to design the shape of metering pin. The numerical model of the landing gear based on planar multibody dynamics are derived. And two-object optimization design of landing gear performance is performed using NSGA-Ⅱ Genetic Algorithm, whose design variables are cross-section diameters at different axial positions of metering pin and whose objective functions are shock-absorbing efficiency and overload factor. Results show that this method can effectively improve shock-absorbing efficiency and reduce overload factor, improve load environment of tires and landing performance. Approach mentioned above is very effective to design a best metering pin of a certain absorber.